A psychological intervention reduces doping likelihood in Italian athletes: A replication and extension - Kavussanu, M.; Rubaltelli, E.; Leo, I.; Hurst, P.; Giovannoni, M.; Barkoukis, V.; Lucidi, F.; D'Ambrogio, S.; Ring, C. (Psychology of Sport and Exercise, 2024)
Research on doping prevention has proliferated in recent years as evidenced by the development of several anti-doping interventions. However, researchers have rarely examined whether an anti-doping intervention delivered and evaluated in one population is similarly effective in a different population. The purpose of our research was to determine whether the psychological intervention developed by Kavussanu et al. (2022) and originally delivered in British and Greek athletes, was equally effective as the standard educational intervention in preventing doping (i.e., by influencing our primary and secondary outcomes) in young Italian athletes. Eligible participants were identified via a screening survey administered to 540 athletes from 46 clubs in Italy. A total of 15 sport clubs (121 athletes; 16.95% female; aged 18.52 ± 2.15 years) were assigned to one of three conditions: a psychological intervention, an educational intervention, or a no-intervention control group. Each intervention consisted of six one-hour sessions delivered to small groups of athletes over six weeks. Athletes completed measures of doping likelihood, anticipated guilt, moral disengagement, and self-regulatory efficacy pre-intervention, post-intervention, and two months later. Control group participants completed the same measures at the same time points. The two interventions were similarly effective in reducing doping likelihood and increasing anticipated guilt from pre to post, while the control group showed no change; these effects were maintained at follow up. Both interventions reduced moral disengagement and increased self-regulatory efficacy from pre to post relative to the control group, and these effects were maintained at follow-up. In conclusion, our study broadly replicates previous findings and highlight the need for anti-doping organisations to target psychological variables and doping-relevant information in anti-doping education.